2015
DOI: 10.1007/s10897-014-9811-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Health Issues for Adults with a Common Genomic Disorder: 22q11.2 Deletion Syndrome

Abstract: Correspondence to: Anne S. Bassett. Conflict of Interest StatementsChrystal Chan, Gregory Costain, Lucas Ogura, Candice K. Silversides, Eva W.C. Chow, and Anne S. Bassett declare that they have no conflict of interest.Human Studies and Informed Consent All procedures followed were in accordance with the ethical standards of the responsible committee on human experimentation (institutional and national) and with the Helsinki Declaration of 1975, as revised in 2000. Informed consent was obtained from all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 55 publications
(121 reference statements)
3
31
0
Order By: Relevance
“…Thirteen studies revealed negative and positive emotions experienced amongst families, caregivers, and patients (Bales et al, 2010a; Briegel et al, 2008; Chan et al, 2015; Costain et al, 2012; Goodwin, Alam, et al, 2017; Goodwin & Mccormack, 2017; Goodwin, McCormack, et al, 2017; Hercher & Bruenner, 2008; Karas et al, 2014; Klingberg et al, 2010; Okashah et al, 2015; Phillips et al, 2017; Reilly et al, 2015). Three subthemes were identified: emotions experienced by parents and caregivers, emotional experiences faced by siblings, shared emotional experiences.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen studies revealed negative and positive emotions experienced amongst families, caregivers, and patients (Bales et al, 2010a; Briegel et al, 2008; Chan et al, 2015; Costain et al, 2012; Goodwin, Alam, et al, 2017; Goodwin & Mccormack, 2017; Goodwin, McCormack, et al, 2017; Hercher & Bruenner, 2008; Karas et al, 2014; Klingberg et al, 2010; Okashah et al, 2015; Phillips et al, 2017; Reilly et al, 2015). Three subthemes were identified: emotions experienced by parents and caregivers, emotional experiences faced by siblings, shared emotional experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Still, patients stated the importance of family support in emotional and practical aspect of living with the disability, in particular, mothers were seen as the primary supporter (Phillips et al, 2017). Contrastingly, inadequate social support was evident in the family and/or spouse of patients who experienced pregnancy and child birth; some were estranged from their families (Chan et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations